A Learning Design to Improve Higher Order Thinking Skills (HOTS) - Ocy Dwi Rismi (Program Studi Pendidikan Matematika jenjang Magister, FMIPA, Universitas Negeri Jakarta, 2021)
The purpose of this research is to describe the learning design aimed at improving students' higher-order thinking skills (HOTS) in learning mathematics and describe the obstacles encountered in the implementation process. The research method used in this study is a literature review. Data analysis uses a descriptive method, which describes the results of the research and then draws conclusions.